Asymmetric reconstruction of mammalian reovirus reveals interactions among RNA, transcriptional factor µ2 and capsid proteins - Muchen Pan (Nature Portfolio, 2021)
Mammalian reovirus (MRV) is a double-stranded RNA (dsRNA) virus that affects the gastrointestinal and respiratory tracts. Here, the authors present the 3.3 Å cryo-EM asymmetric reconstruction of transcribing MRV that reveals the organization of the dsRNA genome, RNA interaction with the polymerase complex, and how the polymerase interacts extensively with its co-factor, µ2, to form a transcription enzyme complex, which engages and regulates RNA transcription.